Exploring Scandinavian approaches to defense budget transparency in Ukraine: A theoretical review of opportunities and challenges - Yuliia Petlenko; Ganna Kharlamova; Vincentas Rolandas Giedraitis; Andriy Stavytskyy; Erstida Ulvidienė (Public and Municipal Finance)
The paper examines the transparency of public finances, with a specific focus on the transparency of Ukraine’s defense budget. The relevance of this study arises from the ongoing war and the increasing public demand for accountability. The study aims to identify concrete measures to address existing gaps in defense budget transparency. The paper applies a comparative methodology, analyzing the feasibility of implementing Scandinavian transparency practices, particularly from Sweden and Norway, which are known for their advanced budgetary oversight mechanisms.The study identifies key challenges, including bureaucratic inertia, limited technical capacity, political constraints, and national security concerns. To address these issues, the paper evaluates strategies such as developing digital budget platforms for real-time access to defense expenditures, participatory budgeting, and enhanced institutional accountability. The results indicate that Ukraine could benefit from secure digital platforms for real-time access to defense budget data, targeted legislative amendments to improve oversight, strengthened institutional capacity for in-depth budget reviews, and public consultations on non-sensitive areas of defense spending to foster public trust.The findings suggest that gradual and context-sensitive improvements in defense budget transparency are both feasible and essential for optimizing resource allocation and strengthening public confidence. By providing a structured approach, this study contributes to the broader discourse on public finance transparency, offering practical recommendations tailored to Ukraine’s specific challenges.